Identifying roles in smoking cessation care for different types of healthcare providers: a qualitative study with people who smoke - van Westen-Lagerweij, Naomi A.; Meeuwsen, Elisabeth G.; Croes, Esther A.; Chavannes, Niels H.; Meijer, Eline (Frontiers in Health Services, 2025)
ObjectiveThis study aimed to explore how people who smoke, in particular those with a lower socioeconomic position, perceive the roles of different healthcare providers in smoking cessation care.MethodsThree semi-structured focus groups were held with a total of 15 people who smoke in community centres situated in low socioeconomic position neighbourhoods in the Netherlands. The focus groups were part of a larger study aimed at improving the delivery of smoking cessation care within primary care. Focus group transcripts were thematically analysed.ResultsParticipants believed it is the role of the general practitioner to initiate a conversation about smoking and inform them about the options for quitting. A quit advice from a medical specialist carried most weight for several participants. Participants felt that pharmacists and doctor's assistants are insufficiently qualified to advise on quitting smoking.ConclusionPeople who smoke and have a lower socioeconomic position seem to have clear ideas about the roles of different healthcare providers in smoking cessation care. These ideas appear to be tied to the perception of whether a healthcare provider is qualified to address smoking.Practice implicationsDoctors can use their authority to address smoking and provide advice. Actions are needed to improve people's perceptions of non-physicians in smoking cessation care.